The role of the multinational firms on the producer services sector: repercusions for peripheral regions - Rosario Asián Chaves (European Regional Science Association (ERSA), 2004)
The spatial polarisation of services is one of the explanations for present regional disparities. A new international division of labour based on Business Services has appeared, in which multinational firms play an important role. This paper aims to examine the repercussions of the behaviour of firms in the advanced business services (ABS) sector on peripheral regions. Particularly, we analyse the case of Andalusia – a region situated in a “central area”, the European Union, but characterised as peripheral-. Using direct research – interviews carried out with a representative sample of enterprises -, we study the impact of these multinational firms, not only from the point of view of the companies which offer these services in Andalusia, but also from the point of view of demand – enterprises which use these services -. Multinational firms Business advanced services Peripheral regions Uneven regional development Andalusia
Keywords: 330